2021
DOI: 10.1002/mma.7495
|View full text |Cite
|
Sign up to set email alerts
|

Padovan and Perrin generalized quaternions

Abstract: In this study, we investigate the Padovan (or Cordonnier) and Perrin generalized quaternions. We obtain the new identities for these special quaternions related to matrix forms. We also introduce Binet-like formulae, generating functions, several summation, and binomial properties concerning these quaternions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It is well known that the sum of the first n terms for the Padovan and Perrin sequences can be given as follows, respectively, Generalizations and some properties of the Padovan sequence can be found in [7][8][9][10][11]. It is the aim of this paper to explore some of the properties of the third-order sequences of thePadovan and Perrin numbers {} n P and {} n R , respectively, and their weighted sums.…”
Section: Wwwjosaromentioning
confidence: 99%
“…It is well known that the sum of the first n terms for the Padovan and Perrin sequences can be given as follows, respectively, Generalizations and some properties of the Padovan sequence can be found in [7][8][9][10][11]. It is the aim of this paper to explore some of the properties of the third-order sequences of thePadovan and Perrin numbers {} n P and {} n R , respectively, and their weighted sums.…”
Section: Wwwjosaromentioning
confidence: 99%
“…. More studies about the quaternions can be found in [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Some properties of Padovan quaternions are studied in [15]. Padovan and Perrin generalized quaternions are determined in [24]. Real quaternions with generalized Tribonacci numbers are examined in [2].…”
Section: Introductionmentioning
confidence: 99%